Mindfulness of Social Studies’ Teachers and Its Relationship to Their Skills of Solving ‎Classroom Problems - Al-Refai ‎, Abeer (Jordan Journal of Educational Sciences, 2021)
The current research sheds light on whether mindfulness meditation would influence the ability to solve classroom problems. More specifically, the study explored the potential correlation between the mindfulness of social studies teachers and their ability to solve classroom problems. The sample of the study consisted of 150 social studies teachers (71 males and 79 females). They were drawn from the population of the study in Irbid Education governorate by using simple random sampling. To achieve that, two scales were used for gathering data; one to measure the mindfulness of social studies teachers and the other to measure their ability to solve classroom problems. Reliability and validity of the study scales were checked. Results of the study indicated that the level of mindfulness of social studies teachers was high with a mean of (4.26). Also, the level of social studies teachers’ ability to solve classroom problems was high with a mean of (3.80). Moreover, there was a positive significant correlational relationship at (α = 0.001) between the level of mindfulness of social studies teachers and their ability to solve classroom problems. The Pearson correlation coefficient was (0.719)